Patient-Centred Care Dentistry And Its Relation With Maqasid Shari’ah: A Narrative Review - Muhammad Annurdin Sabarudin; Muhammad Aunurrochim Mas’ad Salleh; Faizah Abdul Fatah; Haslinda Ramli; Norlela Yacob; Mohd Nasir Abd Majid (USIM Press, 2024)
VOL. 28 NO. 1 Page (1-15)